Automation of technological preparation of manufacture of Open Society "Motor Sich" in the environment of the automated system of the technological manufacture preparations ASTMP on the basis of TechCARD/Search - Богуслаев, А.В.; Мозговой, В.Ф.; Балушок, К.Б.; Реученко, В.А. (Eastern-European Journal of Enterprise Technologies, 2010)
The article is devoted to creation and introduction of the automated system of process design on JSC “Motor Sich” on the base of complex TechCARD/Search. The description of works on introduction of this system, the main principles of construction and functions is cited. Also the description of integration of complex TechCARD/Search with various CAD/CAM systems applied on JSC “Motor Sich” is given.